PENGEMBANGAN PRAKTIKUM DARING REAKSI SUBSTITUSI BERBASIS GREEN CHEMISTRY UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF DAN GENERIK SAINS CALON GURU KIMIA - Sri Mulyanti, - (2022)
This study aims to develop an online experiment of organic compound substitution reactions based on green chemistry, to improve creative thinking skills and generic science of chemistry teacher candidates. The research uses mixed methods, with an embedded experiment model. The research includes experimental procedures and the products are analyzed by GC-MS; making a video in three parts uploaded to Youtube; and implementation of the experimental design using zoom meeting. In the first two meetings, students designed the experimental, and in the next two meetings, students analyzed the experimental video. The number of research subjects in the trial was 21 students and 34 students in the implementation, who were taking organic chemistry experiment courses, at the universities in Semarang city. The data were analyzed quantitatively with the Rasch model, and qualitatively with phenomenological analysis. It was found, the characteristics of the substitution reaction for organic compounds based on green chemistry using menthol with Lucas reagent. GC-MS results showed mentyl chloride produced was 56.63%. Creatively students can design experimental, from reactions, extraction, to identification of mentyl chloride compounds. The implementation of the experimental design has a significant effect on increasing students' understanding of the concept of substitution reactions, as evidenced by the paired t-test of 0.00 < alpha (0.05). Understanding of student concepts has increased in determining the structure of reactant compounds based on products, electron movement mechanisms, determining the position of hydroxyl groups, identification of substitution products based on experimental findings, electron movement mechanisms, and differentiating SN1 and SN2.